2020
DOI: 10.1101/2020.05.01.073387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PSGL-1 inhibits the virion incorporation of SARS-CoV and SARS-CoV-2 spike glycoproteins and impairs virus attachment and infectivity

Abstract: P-selectin glycoprotein ligand-1 (PSGL-1) is a cell surface glycoprotein that binds to P-, E-, and L-selectins to mediate the tethering and rolling of immune cells on the surface of the endothelium for cell migration into inflamed tissues. PSGL-1 has been identified as an interferon-γ (INF-γ)-regulated factor that restricts HIV-1 infectivity, and has recently been found to possess broad-spectrum antiviral activities. Here we report that virion incorporation of PSGL-1 on SARS-CoV and SARS-CoV-2 pseudovirions bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…We found that overexpression of IFITM1 and IFITM2 inhibits SARS-CoV-2 S-mediated VSVpp infection dose-dependently by up to two orders of magnitude, while IFITM3 was less effective ( Figure 1B). As control, we used PSGL-1 a broad-spectrum inhibitor of virus attachment (Fu et al, 2020) and confirmed that it prevents SARS-CoV-2 S-mediated infection (He et al, 2020). None of the IFITMs prevented VSV-G dependent entry ( Figure S1A).…”
Section: Ifitms Block Sars-cov-2 S-mediated Pseudoparticle Infectionmentioning
confidence: 77%
“…We found that overexpression of IFITM1 and IFITM2 inhibits SARS-CoV-2 S-mediated VSVpp infection dose-dependently by up to two orders of magnitude, while IFITM3 was less effective ( Figure 1B). As control, we used PSGL-1 a broad-spectrum inhibitor of virus attachment (Fu et al, 2020) and confirmed that it prevents SARS-CoV-2 S-mediated infection (He et al, 2020). None of the IFITMs prevented VSV-G dependent entry ( Figure S1A).…”
Section: Ifitms Block Sars-cov-2 S-mediated Pseudoparticle Infectionmentioning
confidence: 77%
“…However, a major issue for the VSV-based pseudovirus is the likely presence of residual VSV virus, which may result in high rates of false-positive results 27 . In addition, both VSV-and lentiviral-based pseudoviral particles contain structural components not native to the wild-type SARS-CoV-2, which may alter particle properties in receptor binding and responses to antibody neutralization 15 .…”
Section: Introductionmentioning
confidence: 99%
“…To confirm these results, we repeated the infection using Vero E6 cells that endogenously express ACE2; Vero E6 supports productive SARS-CoV and SARS-CoV-2 infection and is commonly used in studies of coronaviruses (7). Given the low infectivity of pseudoviruses for Vero E6 in the absence of ACE2 overexpression (15,17,18), we also used a Luc reporter pseudovirus, in which the reporter expression is driven by HIV-1 LTR and Tat for higher reporter sensitivity and signal to noise ratio. As shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…To discover potential anti-SARS-CoV-2 activities from TCMs, we screened extracts from approximately 40 TCMs, using a SARS-CoV-2 S protein pseudotyped lentivirus (14,15) and human lung A549(ACE2) target cells, in which the human ACE2 gene is over-expressed through lentiviral vector-mediated stable transduction. The lenti-pseudoviruses use either the green fluorescent protein (GFP) or luciferase (Luc) as the reporter, and were validated with a broadspectrum antiviral entry inhibitor, Arbidol (16), and human antiserum against SARS-CoV-2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation